Pricing and Supply Chain Transparency to Conscientious Consumers - Marco Bertini; Stefan Buehler; Daniel Halbheer (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies how a firm should make pricing and transparency decisions when consumers care about supply chain characteristics. We first show how preferences that account for price and unit cost constrain the firm's pricing power and profit. Surprisingly, we find that the firm may be forced to sell at unit cost under markup aversion. Next, we assume that consumers are uncertain about unit cost and show that, in a pooling equilibrium, it is optimal for both the low-cost and high-cost firm to conceal its unit cost if the cost of disclosure exceeds the corresponding gain from demand expansion. Third, we show that in a separating equilibrium it is optimal for the high-cost firm alone to engage in cost transparency when the increase in product market profit exceeds the cost of disclosure. Finally, we establish the conditions under which it is optimal for the firm to disclose other details of the supply chain including provenance, labor policies, and environmental footprint.
Keywords: D42; L21; M20; M30; 330; conscientious consumption; cost transparency; operational transparency; pricing; reference-dependent preferences